Psoriasis: Epidemiology, Clinical and Histological Features, Triggering Factors, Assessment of Severity and Psychosocial Aspects - Coimbra, Susana; Oliveira, Hugo; Figueiredo, Américo; Rocha-Pereira, Petronila; Santos-Silva, Alice (IntechOpen, 2012)
None